Scientific Life of Hakim Mohammed Azam Khan Rampuri Chashti; Custodian of Indo-Iranian Medicine During the 19th Century Changes of Indian Subcontinent - Hoorieh Afsharipur; Somayyeh Pakbaz; Mahdi Shahriari; Seyyed Alireza Golshani; Alireza Salehi (Tehran University of Medical Sciences, 2021)
Indo-Iranian medicine dates back to a couple of centuries ago. The Gurkanies' movement from Iran and Transoxiana to India introduced the Persian language to India, and the scientific language changed from Arabic and Sanskrit to this language. Iranian medicine has had a remarkable influence on the Indian Subcontinent, a sign of which is the elevated medical literature written in this language. Hakim Mohammad Azam Khan was born in 1813 AD.  His ancestors were great sages of Khorasan (in north east of Iran) and then migrated to Afghanistan and India. Since he lived in the late 19th AD century, he had access to many Iranian traditional books. He provided rich sources of traditional medicine for the next generation by publishing traditional medicine books and traditional pharmacology. He wrote great books such as the Exir Azam (a comprehensive medical encyclopedia), Romouz Azam (a general book on medicine), Qarabadin Azam (Pharmacopeia). With his profound 19th century orientalist approach that emphasized safeguarding the Persian language, he created numerous works in the field of medicine, making him the most serious custodian of Indo-Iranian medicine in India. The present study reviews the scientific life of a contemporary famous author of Indo-Iranian medical literature written in Persian Language.